Rekonstruksi Pemamfaatan Wakaf dalam Meningkatkan Sumber Daya Manusia Bangsa Indonesia - Umaima Umaima (Prodi Ekonomi Syariah IAIN Sorong, 2021)
Currently, Indonesia is faced on problem of low quality human resoorces such as poverty and unemployement. As the majority religion of indonesian society, Islam has responsibility in improving of human resources. Waqf is Islam worship containing two dimentions, namely vertical (Hablun min Allah) and horizontal dimentions (Hablun min al-Nas). Waqf should be able to contribute to improve the human reorces in Indonesia because of It‟s asset reaching 34 Trillions/year. But, in the reality there are many people lifing in proverty. It shows that utilization of waqf is not optimal in Indonesia. There are some ways to realize them, namely utilization in education, health, hospital facilities, development of small and medium enterprises (UKM). With those utilizations, waqf expected to increase the human resources in Indonesia